(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the theoretical and methodological foundations of the art-pedagogical approach based on the ideas of D.B. Elkonin and E.P. Torrance. The psychological and pedagogical essence of creative activity proposed by Elkonin, as well as Torrance’s methods for diagnosing creativity, are examined in an integrated manner. This integration is substantiated as an effective direction for developing the artistic and creative competence of future teachers within the framework of art-pedagogical education. The article presents the theoretical, diagnostic, and integrative stages of the art-pedagogical methodological model and analyzes the results of experimental research. The findings demonstrate that art-pedagogically oriented educational activities significantly enhance students’ creative thinking, aesthetic sensitivity, artistic activity, and pedagogical competence. According to the research results, art pedagogy is considered an effective methodological tool that ensures the unity of theory and practice in the formation of future teachers as creative personalities.